Studi Kasus Perbedaan Karakteristik Mahasiswa di Universitas ‘X’-Indonesia dengan Universitas ‘Y’-Australia - Paramita, Greta Vidya (Bina Nusantara University, 2010)
This research was conducted to highlight the characteristics difference between undergraduate students at Indonesia and Australia. There are many factors that contribute to these differences such as whether or not a student proceed directly to university, whom are paying the tuition fee, and the society’s expectation of the student as an early adulthood individual. These characteristics differences are reviewed using developmental stage theory as the basic reference. It is concluded that students of University ‘Y’ Australia are more independent in deciding what they want, have clearer vision of university life, and knowing what their career plans are after graduating the university. Eventually these differences will take effect to the successfulness of the students study. Therefore it is considered important that related parties, such as the high schools or universities to design a program or activity to prepare their students to undergo university life.